Isolation of bacteriophage from soil sample - Alias, Hafizah (2016)
Bacteriophage also known as phage, is a virus that attack to a specific bacteria and replicates inside bacteria cell to produce more phages. Bacteriophage can be found in sewage, soil, water and food. This virus kills bacteria by lysis the host cell. There are two cycles of phage which are Lytic Cycle and Lysogenic Cycle. The benefits of phage are they can be used to kill bacteria, as replacement of antibiotic, biological control agent, and phage application in food industry. Phage can also survive in any condition because they have ability to reproduce quickly, high level of specificity and long term survivability. Phages were isolated and partially purified using PEG/ NaCl. The titers of phages were determined by plaque assay methods. The soil sample has different population of bacteriophage. Phage is isolate from soil sample to determine what type of phage in soil. From this study, the characteristic of phage showed that the phage is a type of lytic phage because it has similarities with T-type phage.